Feeding of Most Abundant Fish Species in Flemish Cap in Summer 1993 - Rodriguez-Marin, Enrique; Punzón, Antonio; Paz, Xabier; Olaso-Toca, Luis Ignacio (1994)
The stomach contents of 4320 fishes comprising 14 species were collected from Flemish Cap Bank (NW Newfoundland) at depths ranging from 130 to 730 m, during summer 1993. The general feeding intensity was high in all species. Three main feeding patterns were evident: the genus Sebastes consume primarily pelagic species, although they also feed on preys which migrate vertically such as shrimps, Euphausids and mysids. The benthic group is made up of American plaice (Hippoglossoides platessoides), witch flounder (Glyptocephalus cygnoglossus), arctic eelpout (Lycodes reticulatus), wolffishes (Anarhichas lupus and Anarhichas minor) and thorny skate (Raja radiata). Lastly, the group of benthopelagic fish remains, longf in hake (Urophycis chesteri), cod (Gadus morhua), grenadiers (Nezumia bairdi and Macrourus berglax) and Greenland halibut (Reinhardtius hippoglossoides). Pelagic and benthopelagic preys are an important food resource for all fish considered, the abundance of Hyperids, P. borealis and Sebastes sp. in summer makes them an important food resource in the diet of fish in Flemish Cap.